ANALISIS PROFIL PETERNAK TERHADAP PENDAPATAN PETERNAK BABI DI KECAMATAN LINTONG NIHUTA KABUPATEN HUMBANG HASUNDUTAN - beny g Mulya (Universitas Sumatera Utara, 2013)
The research was conducted at the Kecamatan Lintong Nihuta, Kabupaten Humbang Hasundutan of North Sumatra, which began on 10 July to 24 August 2012. The purpose of this study was to analyze the income pig farmers, and at Humbang Hasundutan Kecamatan Lintong Nihuta. The research methods use is survey methods with a unit that maintains a family pig farmer. The sampling method used is Proportional Stratified Random Sampling is by way of selecting three village is the Desa Sigompul, Desa Hutasoit 2, Desa Nagasaribu 4. Samples from this study amounted to 60 families of pig cattle breeders obtained from 30% of farmers in each village, the Desa Sigompul (14 farmers), Desa Hutasoit 2 (21 farmers) and Desa Nagasaribu 4 (25 farmers). Based on research results obtained that business scale, farming experience, and number of dependents has a positive effect on pig cattle breeders. Where as the breeder age, educational level, and the amount of labor has a negative effect on Pig cattle breeders in the Kecamatan Lintong Nihuta Kabupaten Kabupaten Humbang Hasundutan.